Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis - LoBue, Christian (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n =3,187) and normal cognition (n=3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-e4 (Apoe4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p<.01) and associated with increased odds of MCI diagnosis in unadjusted (OR=1.25; 95% CI =1.05 – 1.49) and adjusted models, accounting for age, education, Apoe4, and a composite vascular score (OR=1.32; 95% CI=1.10 – 1.58). This association, however, was largely attenuated (OR=1.14; 95% CI=0.94 – 1.37; p=.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p<.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p =.13) when sex and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as sex and depression and requires further investigation.